2004
DOI: 10.1073/pnas.0401827101
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of repressor element 1 silencing transcription factor/neuron-restrictive silencing factor (REST/NRSF) target genes

Abstract: The completion of whole genome sequencing projects has provided the genetic instructions of life. However, whereas the identification of gene coding regions has progressed, the mapping of transcriptional regulatory motifs has moved more slowly. To understand how distinct expression profiles can be established and maintained, a greater understanding of these sequences and their trans-acting factors is required. Herein we have used a combined in silico and biochemical approach to identify binding sites [represso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
499
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 440 publications
(531 citation statements)
references
References 41 publications
26
499
2
Order By: Relevance
“…ac.uk/cgi-bin/RE1db/nrse.cgi) [7], the following putative targets: (1) the gene encoding the soluble N-ethylmaleimidesensitive factor attachment protein receptor (SNARE) protein SNAP25, which contains two consecutive RE-1s, referred to as RE-1.1 and RE-1.2 [7]; (2) the genes encoding the members of the Ca 2+ sensor synaptotagmin family SYT II, SYT IV, SYT VI, SYT VII, SYT IX; and (3) the genes coding for the N-ethylmaleimide-sensitive factor (NSF), for UNC-18 homologue 1 (MUNC-18-1) and for complexin II, which participate in the formation and stabilisation of the SNARE complex. The 21 bp human RE-1 sequences associated to these genes were compared with those of consensus RE-1 and of the known CX36 RE-1 [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ac.uk/cgi-bin/RE1db/nrse.cgi) [7], the following putative targets: (1) the gene encoding the soluble N-ethylmaleimidesensitive factor attachment protein receptor (SNARE) protein SNAP25, which contains two consecutive RE-1s, referred to as RE-1.1 and RE-1.2 [7]; (2) the genes encoding the members of the Ca 2+ sensor synaptotagmin family SYT II, SYT IV, SYT VI, SYT VII, SYT IX; and (3) the genes coding for the N-ethylmaleimide-sensitive factor (NSF), for UNC-18 homologue 1 (MUNC-18-1) and for complexin II, which participate in the formation and stabilisation of the SNARE complex. The 21 bp human RE-1 sequences associated to these genes were compared with those of consensus RE-1 and of the known CX36 RE-1 [11].…”
Section: Resultsmentioning
confidence: 99%
“…However, increasing evidence suggests that the significance of the REST/RE-1 system is diverse in embryonic and adult cells and depends on the range of target genes that REST interacts with. Accordingly, a bioinformatic analysis recently revealed about 1,800 putative REST target genes within the human genome, with attributed roles ranging from transcriptional regulation through to metabolism and various aspects of neuronal function [7]. Previous reports have identified some of these target genes and their function in and outside the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…As siRNA-mediated knockdown of NRSF/ REST correlated with increased AKT phosphorylation (Westbrook et al, 2005), we analysed genomic sequences of AKT pathway members for the presence of NRSEs. On analysing the 3 0 untranslated region of the AKT2 gene, a putative NRSE was confirmed, 15 kb from the transcription start site (Bruce et al, 2004). This NRSE of AKT2 (ATCAGCACCGGGGACAGCGCG) showed high similarity to the core sequence (TTCAG CACCACGGACAGCGCC) (Schoenherr and Anderson, 1995).…”
Section: Nrsf/rest As a Putative Tumour Suppressormentioning
confidence: 88%
“…As NRSEs were identified for the rat SCG10 and other neuronal genes, NRSF was initially regarded as a master negative regulator of neurogenesis (Schoenherr and Anderson, 1995). Indeed, the number of putative NRSF/REST-regulated genes has dramatically risen since (Bruce et al, 2004). A recent study showed that the canonical 21-bp consensus sequence of NRSE represents a subgroup of an even larger set of NRSEs, which also contains elements compressed by 1-2 bp and those extended by 3-9 bp (Otto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To address the latter part of the question, PcG, is normally (but not always) associated with silenced genes (stem cells provide an interesting exception) whereas our studies (Belyaev et al, 2004;Bruce et al, 2004;Greenway et al, 2006) show that REST is normally associated with active genes, i.e., employment of REST can maintain repression of an otherwise active gene, whereas in the differentiated state, PcG normally acts to establish and/or maintain silence. G.C.…”
Section: Do You Think That Many Developmental Decisions Are Epigenetimentioning
confidence: 70%